Prototype Of DPO Search Information System (People Search List) On CCTV Cameras Using Face Recognition - Anugraha, Tri Reski; Dedy Atmajaya; Lilis Nur Hayati; Anugraha, Nurhajar (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The efficiency aspect of the housing security sector is the main consideration in creating information technology in a CCTV security development, because so far CCTV has not guaranteed maximum housing security, because CCTV can only record not analyze. This makes CCTV only a recording device for the point of occurrence, so this activity is less effective considering CCTV cannot analyze the face of a person who has committed a DPO action. So on that basis, researchers are developing existing technologies with facial recognition systems using the face recognition method for housing security. This method works by detecting a person's facial features. The face recognition apps provide information to the authorities by notifying the notification on the user's smartphone (security guard). So face recognition apps have been applied to the Green Cakra Housing, to help security guards monitor the entrance and exit of guests in the housing. This system can recognize the face of DPOs by obtaining a percentage of the assessment as much as agreeing that the application is effective enough.